People and ergonomics in a lean methodology: a case study - Maia, Laura Costa (2019)
Nowadays Lean Production is a management methodology implemented in many industries and services. Nevertheless, Lean is more than a management methodology; it is a philosophy and a new way of life. This is the reason why it is difficult to implement it but, even worse, to make it successful and sustainable A continuous effort of improvement must always be keep in mind Attending to these factors, it is important to have a methodology that helps to effectively implement LP. Bearing this in mind, in the scope of a PhD research work, a new methodology was developed, named PESO, oriented for the Textile and Clothing Industry (TCI). The designation PESO comes from four dimensions to take in account when implement LP: People, Ergonomics, Sustainability and Operational performance. Normally, a Lean methodology should be different from industry to industry in order to model the differences and peculiarities of them and, most importantly, to assure that Lean implementation will be maintained PESO methodology is divided in three phases and in each phase many tools should be used. This methodology was validated in three case studies in the TCI companies located in the North of Portugal. This paper aims to present some results on the implementation of this methodology in a case study, mainly related with People and Ergonomics dimensions.